Is There Still a Lebanon? - Malik, Habib C. (1997)
Lebanon has been a hard country to understand since the outbreak of its fifteen-year conflict in 1975. Was that a civil war or an international one? Who were the protagonists, the Left and Right, the Christians and Muslims, or some other parties? The debate continues today. Is it the case, as the National Geographic puts it, that "Peace and a drive to prosper now unite many former foes in efforts to rebuild" the country?1 Or are the former foes quiescent because they are repressed? Is Lebanon a fully functioning government, as the State Department holds, or "the world's only remaining satellite state," as Representative Benjamin Gilman (Republican of New York) puts it?2 To understand the nuances of today's Lebanon means looking critically at several key issues, including the Syrian occupation, civil society, and the religious communities. From this we can draw conclusions about the future and about U.S. policy.